USING DIGITAL VIDEO TO RAISE STUDENTSâ MULTI-LITERACIES IN TEACHING ENGLISH FOR YOUNG LEARNERS - Irawati, Lulus (English Teaching Journal, 2014)
Teaching English for Young Learners is not as simple as people thought. There are a lot of things toconsider. One of them is fostering young learners to be multi-literate. It means that they need to master more than one skill in their life. The skills or abilities are listening, speaking, reading, writing, counting, et cetera, with the sources either from hardcopy (books) or softcopy (internet). Therefore, it is needed a medium to help the young learners to achieve multi-literacies, that it is a digital video. This mini-research aimed to use digital video to raise studentsâ multi-literacies in TEYL, by utilizing descriptive qualitative design. The mini-research was conducted in English course for the age of 9-10 years old. It was done for a month in total of 4 meetings, with duration about 60 minutes. The teacher was successful to use digital video combined with picture series.Â  The students felt happy and interested, since they firstly watched the digital video âsleeping beautyâ before being asked to arrange picture series. The teacher also explored some vocabulary in the video and tried to contrast them with reality in surrounding. The kind of activity helped the young learners to communicate cross culturally. Â In Â fact, Â communicating Â cross Â culturallyÂ  was Â also Â one Â of Â additional Â skill Â that indicated the students as multi-literate people. All in all, based on the findings of interview, the researcher also recommended conducting further research.